SUSCEPTIBILITY OF 686 STRAINS OF BETA-HEMOLYTIC STREPTOCOCCI ISOLATED FROM CASES OF PHARYNGITIS TO FIVE ANTIBIOTICS IN VITRO - R. A. Gharagozloo; F. Darougar (Tehran University of Medical Sciences, 1974)
This study was undertaken to determine the antibiotic sensitivity of 686 strains of hemolytic streptococci isolated at the School of Public Health, Division of Streptococcal Studies, to five antibiotics in vitro. All of the strains were sensitive to penicillin, erythromycin, chloramphenicol and ampicillin. 27 (4%) of the strains, were resistant to tetracyclin. The clinical implications of this study, particularly in the light of information from other areas, emphasize the fact that, if the blind treatment of acute upper respiratory tract infection with tetracycline were ever justified it has certainly ceased to be so.